Enhancing Collaborative Learning and Academic Achievement through the Team Games Tournament (TGT) Strategy among University Students in English Language Instruction - Cristian Anggraini; Laily Fajariyah; Lailiy Kurnia Ilahi; Endang Agus Sulasmi; Tutik Kurniawat; Wahyudi Wahyudi (PT. Intelek Cendikiawan Nusantara, 2025)
English language instruction is a core component of higher education curricula, designed to develop students' proficiency in academic reading, writing, speaking, and listening. However, university classrooms often face challenges such as low student engagement and insufficient collaboration, leading to suboptimal learning outcomes. This study aims to explore the effectiveness of the Team Games Tournament (TGT) cooperative learning strategy in enhancing student collaboration and academic performance in an English language course for undergraduate students. The research adopts a Classroom Action Research (CAR) approach using the Kemmis and McTaggart spiral model, consisting of planning, action, observation, and reflection across two intervention cycles. Data were collected through classroom observation and student interviews and analysed through interactive and reflective techniques. Participants included 25 second-semester students enrolled in an English for Academic Purposes (EAP) course. Findings indicate a notable increase in student collaboration, from 45% in Cycle I to 88% in Cycle II, as well as a significant improvement in academic achievement, with mastery levels increasing from 12% to 92% across the two cycles. The results suggest that the TGT strategy creates an engaging and interactive learning environment, promoting both social interaction and deeper language acquisition